Design, Synthesis and in vitro Anticancer Activity of a Cu(II) Complex of Carminic Acid: A Novel Small Molecule Inhibitor of Human DNA Topoisomerase I and Topoisomerase II. Issue 21 (19th December 2016) - Das, Piyal; Jain, Chetan Kumar; Roychoudhury, Susanta; Majumder, Hemanta Kumar; Das, Saurabh
Abstract: The hydroxy‐9, 10‐anthraquinones in anthracyclines form semiquinones and reactive oxygen species (ROS) that help in antitumor activity. ROS generation is cytotoxic to cells but cardiotoxic as well. Carminic acid (CA) with a sugar bound to a hydroxyanthraquinone resembles anthracyclines closely. Role of sugar in anthracyclines was realized from physicochemical parameters of CA that were found to be in between those of anthracyclines and hydroxy‐9, 10‐anthraquinones. A Cu(II)complex of CA was prepared and its structure attempted from powder X‐ray diffraction. Studies with DNA revealed unlike CA, the complex did not show decrease in binding constant with increase in the pH of the medium. DNA relaxation assay showed the complex as a dual inhibitor of human DNA topoisomerase I and topoisomerase II stabilizing covalent topoisomerase‐DNA adducts in vitro. Inhibition of growth of ALL‐MOLT‐4 cells was higher for the complex supporting in vitro experiments. An enzyme assay revealed less superoxide formation for the complex suggesting that it might be less cardiotoxic. Decrease in superoxide for the complex does not affect anticancer activity, which was greater than CA. Abstract : Anthracycline drugsform reactive oxygen species useful for cytotoxicity but responsible for cardiotoxic side effects. Carminic acid, a small molecule analogue of anthracyclines, helped to realize role of sugar in cancer chemotherapy.Studies on theCu(II) complex of carminic acid with DNA revealed unlike carminic acid, the complex did not show a decrease in binding constant with increase in pH.The complex is a dual inhibitor of human DNA topoisomerase I and II.Inhibition ofgrowth was higher for the complex on ALL‐MOLT‐4 cells. An enzyme assay revealed less O2 − formation by the complex suggesting itwould be less cardiotoxic.Decrease in O2 − formation did not affect anticancer activity.